The Influence of Refugee Students' Personal Characteristics on Study Success in Online Education - F. Reinhardt; T. Deribo; O. Zlatkin-Troitschanskaia; R. Happ; S. Nell-Müller (Journal of International Migration and Integration, 2020)
There is little research on the study success factors of refugee students in higher education. One approach to meeting the growing global demands is to provide online education specifically for refugees. This study examines specific personal characteristics of refugee students and their influence on success and retention in online education. Individual factors such as intrinsic motivation and language proficiency, cognitive functioning, and sociodemographic factors such as gender and country of residence influence retention of refugee students during online studies. The results indicate that sociodemographic factors (e.g., gender), cognitive factors (e.g., English proficiency), and external factors (e.g., country of residence) have a significant influence on study retention on refugee students.
Keywords: 300; Higher education; MOOCs; Online education; Refugee education; Study success factors